POPULIST LEFT-WING FOREIGN POLICY: THE CASE OF KIRCHNERISM IN ARGENTINA - Colalongo, Rodolfo; Donato, Stellamarina (Cultura Latinoamericana, 2021)
This article addresses the issue of populist foreign policy in Argentina and employs a multi-methods research that combines discourse analysis, foreign policy analysis, and historical political reconstruction of Kirchnerism. Theoretically, we refer to populism as an “Ideational Approach” and we consider Destradi and Plegaman’s thematic lines in order to investigate populism in world politics. Throughout the paper, we argue that left-wing populist foreign policy does not discriminate against international cooperation and globalization per se but in a Manichean vision of the world, it criticizes western rich countries, and proposes the creation of new regional alliances.